Model Pembelajaran Daring Dengan Pendampingan Orang Tua - Andy Sapta; Abdul Hamid; Edi Syahputra (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study was to develop an android application-based parenting mentoring learning model that is suitable for use for seventh grade students of SMP Negeri in Kisaran city. The method used in this research is a research and development model. The population in this study were all grade VII (seven) public junior high schools in Kisaran in the 2019/2020 school year. The steps (syntax) of this learning model are the SAPTA learning model, as follows: (1) Schedule (learning design phase); (2) Acceptance (feedback phase); (3) Performance (assignment phase); (4) Transmit (information delivery phase); (5) Assistance (parental assistance phase). This research produces a learning model based on parental assistance assisted by an android application and its supporting devices that are feasible to support learning activities, especially online learning. The resulting learning devices are an android application to assist parents in learning, model books, teacher manuals, and parent manuals. Through this research, it has also been proven that the product developed has a positive impact. Namely, it can significantly increase the achievement of students' independent learning outcomes. It can be concluded that the learning model based on parental assistance assisted by an android application that was developed was considered feasible, effective, and practical to use for class VII SMP Negeri in Kisaran city.